Cognitive P300 Potential in Retired Sportsmen with a Career in Contact Sports - Iliya. Valkov; Rositza Dimkova (Journal of Biomedical & Clinical Research)
Eleven retired sportsmen, who had a career in contact sports (three boxers, four footballers, four wrestlers) and one cyclist with a history of several falls from a bicycle and had been diagnosed with a cerebrovascular trauma, were investigated with auditory cognitive P300. The age range was aged between 26 and 63 years. Ten out of the twelve presented cognitive wave latency between 512 msec and 928 msec. This finding made us conclude that repetitive minor head injuries (mHI) that they inevitably had experienced during their carrier has led to cognitive problems in older age.